Pemanfaatan Media Sosial Dalam Komunikasi Politik: Propaganda Isu Sistem Pemilu Proporsional - Samad, M. Yusuf; Hilman, Ferdi; Andi Yakub; Yoda, Imam Ali; Harahap, Ongku Sutan (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
The polemic on the proportional election system ahead of the election continues to emerge. Approaching the 2024 elections, this polemic has re-emerged and has been spearheaded by political actors as political communicators. These communicators use their social media as a forum for conveying propaganda regarding the proportional election system. This study aims to analyze the political communication of political actors involved in the polemic on the issue of a proportional election system ahead of the 2024 Election and how propaganda techniques on social media are related to this issue. This study was conducted to explore patterns of political communication related to the proportional election system delivered on Twitter. This study applies qualitative content analysis or Qualitative Content Analysis (QCA). The study results show that political communicators use social media Twitter to carry out propaganda about the proportional electoral system by using the Testimonial propaganda technique, Card-stacking Frustration, or Scapegoat.